Fast seed histology protocols: Benzene derivatives-free vs xylene-dependent - Benavides-Acevedo, M.; Torres-Segura, J. (Agronomía Mesoamericana, 2022)
Introduction. Seeds are complex structures that allow the biological and crop propagation of plants. Seed histology can be used for teaching, researching, and for pathological diagnostic. Histology protocols are commonly divided into 5 different stages: fixation, processing, cutting, staining, and mounting. Xylene is a dangerous reagent used during the processing, staining, and mounting of histological specimens that can contaminate the environment and is toxic for users. Objective. To compare two new protocols for seed histology accelerated with microwave, tested on seeds of economic importance species. Materials and methods. The experiments were done between January and May of 2022 at the Centro de Investigaciones en Granos y Semillas (CIGRAS) of the Universidad de Costa Rica. The compared protocols were: a benzene derivatives-free (BDF) and a xylene-dependent (XD). Seeds of Carica papaya L. (Caricaceae) var. Pococí, Coffea arabica L. (Rubiaceae) var. Obata, Glycine max L. (Fabaceae) var. CIGRAS-06, Phaseolus vulgaris L. (Fabaceae) var. Tayni, Oryza sativa L. (Poaceae) var. Lazarroz FL, and Zea mays L. (Poaceae) var. EJN-2 were used. Three technical replicates of five seeds of each species were tested with the XD and BDF protocols, on different days each replicate. Results. The photomicrographs obtained with both protocols showed that the samples maintained the morphology integrity of embryo, endosperm or cotyledons, and other seed structures. BDF and XD protocols produced seed histology slides and microphotographs. PAS-Coomassie Blue staining made a good differentiation of carbohydrates and proteins. Fastness of both protocols is a benefit compared with other protocols for plant histology that can take several days or even weeks. Conclusions. The BDF and XD protocols were suitable for seed histology analysis of bean, coffee, maize, papaya, and soybean, slides were obtained in less than 5 hours. BDF protocol is the first for plant tissue processing that does not use benzene derivatives and that uses paraffin as embedding medium.